SensorsConnect Framework: World-Wide Web for Internet of Things - Abdelrahman Elewah; Khalid Elgazzar (IEEE Access)
The widespread adoption of the Internet of Things (IoT) has led to a surge in smart sensing devices connected to the Internet. While IoT enables machines, embedded systems, and appliances to access the Internet, they do not interact with it as humans do through the World Wide Web (WWW). Unlike humans, IoT devices lack a unified framework like the WWW for collaboration and data sharing. This is primarily due to 1) separate infrastructure often required for IoT security and privacy and 2) challenges of limited connectivity, device heterogeneity, and evolving technology. This paper presents SensorsConnect, a system that connects IoT devices in a WWW-like framework, enabling real-time sensing data searches across a broad IoT context. It defines the architecture, core processes, and major challenges of SensorsConnect, along with strategies to address these challenges. A motivating scenario illustrates its potential impact in real-life situations, such as finding a drive-thru coffee shop or crossing a country border. Using real-time road status and service occupancy data, SensorsConnect enhances Google Maps service recommendations, not only minimizing customer wait times but also distributing workload more evenly across service points. Performance evaluation shows that SensorsConnect reduces average service times by 46% at drive-thru locations and 31% at border crossings compared to Google Maps. This promising application could improve public access to live data, supporting real-time decisions and enhancing quality of life.